A new polymorphic species of egg-brooding frog of the genus Fritziana from southeastern Brazil (Anura: Hemiphractidae) - Walker, Marina [UNESP]; Gasparini, Joao Luiz; Haddad, Celio F. B. [UNESP] (Deutsche Gesellschaft Herpetologie Terrarienkunde E V, 2016)
We describe a new species of egg-brooding frog of the genus Fritziana from the Atlantic Forest in the state of Espirito Santo, Brazil. The new species was historically considered to represent Fritziana goeldii, but is diagnosed by having small snout-vent length for the genus, snout tip mucronate, limbs striped, distal subarticular tubercles simple and round on all fingers and toes, open dorsal pouch in females carrying eggs, and tadpoles deposited in bromeliads. It is also the first species of the genus to exhibit two distinct dorsal patterns: 1) a triangle covering the entire dorsum or 2) an interorbital triangle with a short V beginning at its apex. New molecular data is provided and used for comparing the new species with topotypes of three other species of the genus.
Keywords: Amphibia; Atlantic Forest; Fritziana goeldii; polymorphism; DNA analysis